Stormdancer - Kristoff, Jay (Kristoff, Jay. Lotus war, 2012)
In this dystopian steampunk fantasy set against a backdrop of feudal Japan, warrior Yukiko captures a supposedly extinct (but crippled) griffin for the Shogun, then learns -- after meeting secretive Kin and the rebel Kage cabal -- of the horrifying extent of the Shogun's crimes, both against her country and her family. Returning to the city, Yukiko is determined to make the Shogun pay -- but what can one girl and a flightless griffin do against the might of an empire?